Black mirror : the cultural contradictions of American racism - Lott, Eric (The Belknap Press of Harvard University Press, 2017)
Black Mirror explores the ways U.S. cultural institutions--classic American literature, Hollywood film, pop musical artistry, venturesome social commentary--have relied insistently and repeatedly on racial symbolic capital, including and above all blackface, to reproduce white cultural dominance. In the process these forms have threatened to betray the racial hegemony that generated them and that they exist in order to maintain. Hence the subtitle, The Cultural Contradictions of American Racism. In a series of chapters addressing such arts and artists as Mark Twain, film noir, Joni Mitchell, Elvis impersonators, Bob Dylan, and Barack Obama, Black Mirror locates the symbolic surplus value that accrues to white cultural producers and institutions whenever they traffic in "blackness"--A political economy of the sign that can sometimes surprise us (not least by producing a black president).--